Presence of stress and other risk factors for cardiovascular disease among nurses and lawyers of a city of Minas Gerais - Brazil - Aline Daniele Santana Silva; Olga de Fátima Leite Rios; Aline do Carmo França-Botelho (Universidad de Alicante, 2018)
Cardiovascular disease (CVD) is an important cause of morbidity and mortality worldwide. This study aimed to evaluate stress and other risk factors for CVD in nurses and lawyers of a municipality of Minas Gerais (Brazil). The sample consisted of 20 nurses from the hospital area and 26 independent lawyers. Each volunteer answered two questionnaires, one on risk factors for CVD in general and the Inventory of Stress Symptoms for Adults (ISSL). After it was found the body mass index (BMI), abdominal circumference (AC) and blood pressure of each volunteer. The results indicate that 55% of nurses and 30.9% of the lawyers present stress. The exhaustion stage is of particular concern, being found, respectively, 10% and 11.6% of nurses and lawyers. The findings relating to overweight / obesity, waist circumference of risk, sedentary lifestyle and intake of alcohol are worrying because increase the risk of CVD in the sample. It was concluded that there are risk factors for CVD and interventions are needed to improve health and quality of life of these professional.